SOIL WATER RETENTION CURVE DETERMINATION of ARTIFICIAL SOIL USING TENSIOMETER - Dwi Sarah (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2006)
Soil water retention curve possesses a significant importance in unsaturated soils engineering. The emergence of high capacity tensiometer has provided an alternative technique for the determination of the soil water retention curve.  In this study soil water retention curve was obtained by stage drying technique. Possible factors affecting the accuracy of this technique were discussed.